Colour degradation of artworks: an ab initio approach to X-ray, electronic and optical spectroscopy analyses of vermilion photodarkening. Issue 3 (24th November 2014) - Hogan, C.; Da Pieve, F.
Abstract : First principles calculations explain the presence, colour, and photo-reactivity of Hg-containing compounds involved in vermilion degradation. Abstract : Light-induced photodarkening of the pigment vermilion (α-HgS, cinnabar), observed in historical museum paintings and in murals at archaelogical sites worldwide, is an intriguing phenomenon that has triggered intense study using microscopy and spectroscopy techniques. However, the origins of the degradation and the nature of the concomitant physical, chemical and structural transformations are not yet completely clear. We present a first-principles study based on state-of-the-art electronic structure methods which sheds light on this darkening phenomenon. The presence of secondary compounds proposed to form during the transformation of vermilion (Hg3 S2 Cl2 polymorphs, Hg2 Cl2, and HgCl2 ) is confirmed using X-ray spectroscopy simulations, and their structural, electronic, and optical properties are analysed using different levels of theory and compared with experimental observations. A scheme for growth of α-Hg3 S2 Cl2 on α-HgS is proposed, and possible formation and decomposition paths for the mercury chlorides are discussed. Approximations used in computing band gaps and band edges are examined in detail. This work highlights the key role that first-principles methods can play in the application of materials science to art conservation.